A leap in scale for invasive species management: a medium-scale beaver eradication pilot project - Jusim, Pablo (2024)
In 1946, 20 beavers (Castor canadensis) were introduced in Tierra del Fuego, Argentina, and over the last 70 years, the population has expanded, severely affecting riparian environments. In 2008, Argentina and Chile agreed to restore the environments affected by beavers through their eradication. The objectives of this paper were to assess the trapping effort and cost required to remove beavers, and to determine the factors that influence capture success. The study was conducted over 7 pilot areas in the Argentine part of Tierra del Fuego. Ten trappers using body-grip traps, snares, and shooting carried out an eradication pilot project between October 2015 and June 2018. Trappers acted in 505 colonies, performing 9,751 trapping episodes, and capturing 1,012 beavers. In the mountain range zone, trappers needed on average 23 trapping episodes/km of watercourse. Capture success was best explained by trap placement and trap type. We estimated a required investment of 31 million US dollars over 17 years for a full beaver eradication in the Argentine part of Tierra del Fuego. We concluded that by using mainly body-grip traps, eradication is feasible and it allows trapping in neighboring colonies simultaneously, without the need to check traps daily. Traps should be set preferably on dams, dams should be broken only after the first captures, and trappers should be trained to capture all individuals.